Tide and Tidal Current Prediction by High Speed Digital Computer - Harris, D. L.; Pore, N. A.; Cummings, R. A. (The International Hydrographic Review, 2015)
The Tide and Tidal Current Tables of the U. S. Coast and Geodetic Survey for 1966 have been computed and edited by a digital computer, the IBM 7094. Prediction by this method is found to be more economical and expedient than by the tide prediction machine in use since 1910. The shift to digital predictions has been gradual. The first program was prepared in 1956 to predict hourly tide heights only, for use in storm surge research. The greatest advantage to digital prediction at that time was the elimination of the hour or more required to set up a new problem on the tide predicting machine, when highly accurate predictions were needed for many short periods. Later, as more efficient computers became available, this program was expanded to include the computation of highs and lows, editing the data in a form suitable for publication and the complete prediction and editing of the tidal current tables. The existing program, to a large degree, reproduced the same calculations formerly made on the analogue tide predicting machine, and with comparable accuracy. The greater versatility of this system invites experimentation, not feasible with the analogue computer. Thus, it is expected that in the long run the switch to digital calculations will lead to an increase in the accuracy of the predictions for stations having complex tide problems. The program grew through the years, and is not the most efficient that could be prepared today. Nevertheless, it appears doubtful that the improved efficiency would justify a complete revision. This report gives a general description of the program, the input data specifications and samples of the results.